Perinatal depression trajectories and child development at one year: a study in China - Yuan Zhu; Xiaoyu Li; Junyu Chen; Wenjie Gong (BMC, 2024)
Abstract Background The objective of the current study was to investigate the correlation between trajectories of maternal perinatal depression (PND) spanning from early pregnancy to one year postpartum and developmental delays observed in one-year-old children. Methods The dataset under examination encompassed 880 women who took part in a mother-child birth study conducted in China. Latent class growth analysis (LCGA) was employed to identify patterns in Edinburgh Postnatal Depression Scale (EPDS) scores of women, spanning from early pregnancy to one year postpartum. To assess the neurodevelopment of one-year-old children, a Chinese version of the Bayley Scale of Infant Development (BSID-CR) was employed. Logistic regression was employed to explore the association between PND trajectories and developmental delays in children, with appropriate covariate adjustments. Results The trajectories of maternal PND identified in this study included a minimal-stable symptom group (n = 155), low-stable symptom group (n = 411), mild-stable symptom group (n = 251), and moderate-stable symptom group (n = 63). Logistic regression analysis revealed that mothers falling into the moderate-stable symptom group exhibited a notably heightened risk of having a child with psychomotor developmental delays at the age of one year. Conclusions The findings drawn from a representative sample in China provide compelling empirical evidence that bolsters the association between maternal PND and the probability of psychomotor developmental delays in children. It is imperative to develop tailored intervention strategies and meticulously design mother-infant interactive intervention programs for women with PND.